Quasi Fe MIL-53 nanozyme inducing ferroptosis and immunogenic cell death for cancer immunotherapy - Yan, Zihui; Bai, Yang; Zhang, Songtao; Kong, Lingyi; Wang, Yu; Sun, Huilin; Li, Yi; Qiu, Lin; Zhang, Ruijie; Jiang, Pengju; Zhao, Donghui; Chen, Zhongyan; et al. (Nature communications, 2025)
Nanozymes offer diverse therapeutic potentials for cancer treatment which is dependent on the development of nanomaterials. Quasi-metal-organic framework is a class of metal-organic framework-derived nanomaterials with a transition state from metal-organic frameworks towards metal oxide featuring porous structure and high activity. Herein an iron-based quasi-metal-organic framework nanozyme Q-MIL-53(Fe) is reported via a controlled deligandation strategy, exhibiting enhanced peroxidase-/catalase-mimic activity and glutathione depletion capacity, whose underlying mechanisms are studied via density functional theory calculations. Q-MIL-53(Fe) demonstrates biocompatibility and superior antitumor efficacy compared to pristine MIL-53(Fe). It can activate antitumor immune response by inducing ferroptosis and immunogenic cell death, promoting dendritic cell maturation and T lymphocytes infiltration. Furthermore, a combination of Q-MIL-53(Fe) and programmed cell death protein 1 antibody amplifies cancer immunotherapy. This study validates the antitumor activity of quasi-metal-organic frameworks and its immunotherapy induction potential. It would broaden the application of quasi-metal-organic frameworks and open avenues for developing antitumor nanozymes. Nanozymes offer diverse therapeutic avenues for cancer treatment. In this work, the authors report an iron-based quasi-metal organic framework nanozyme Q-MIL-53(Fe) with enhanced peroxidase and catalase-mimicking activity and glutathione depletion capacity and use it for tumor immunotherapy via inducing ferroptosis and immunogenic cell death.